Improving quality of diabetes care by integrating psychological and social care for poorly controlled diabetes: 3 Dimensions of Care for Diabetes. (January 2016) - Doherty, Anne M; Gayle, Carol; Morgan-Jones, Ruth; Archer, Nicola; Laura-Lee; Ismail, Khalida; Werner, Anne
Objective: Many people with persistent suboptimal diabetes control also have psychiatric morbidity and social problems which interfere with their ability to self-manage their diabetes. Current models of care in the UK do not integrate these different dimensions of care or address inequalities between physical and mental health. 3DFD (3 Dimensions of Care For Diabetes) integrated medical, psychological, and social care in diabetes for patients with persistent suboptimal glycemic control (HbA1c > 75 mmol/mol) despite guideline-based routine diabetes care, to improve glycemic control, reduce psychological distress, and improve social functioning. Methods: The service delivered interventions including brief psychological therapies, mental health assessments, psychotropic medications, and social support, enhanced by patient-led case conferences aiming to optimize diabetes care. 3DFD measured changes in HbA1c, psychological functioning, quality of life, rates of unscheduled care, and levels of engagement with routine diabetes care at baseline and at 12 months. Conclusion: At 12-month follow-up, 3DFD patients achieved significant reductions in HbA1c of 15 mmol/mol, International Federation of Clinical Chemistry (1.4% Diabetes Control and Complications Trial) and improvements in depression scores and patient satisfaction. This model of care demonstrates that integrated care can improve diabetes outcomes in people with psychological and social comorbidities.